Unveiling the nexus between environmental exposures and testicular damages: revelations from autophagy and oxidative stress imbalance - Xiuwen Kong; Xinda Wang; Qiushi Xia; Qingqing Hu; Wenqian Yu; Qiuru Huang; Jiaxin Li; Chenyu Wang; Ziwen Lin; Yiheng Liu; Yujuan Qi; Xiaofang Tan; et al. (Cell Death Discovery)
Abstract Recent evidence consolidates the deleterious impact of environmental exposure on testicular damage. Environmental exposures can instigate testicular toxicity, causing damage to the Sertoli-Sertoli cell-mediated blood-testis barrier (BTB) integrity, alterations in hormone levels orchestrated by aberrant Leydig cells, and disruption of spermatogenesis. Despite diverse study designs and methodologies, a consensus is emerging on how environmental factors induce oxidative stress by elevating ROS levels, affecting autophagy through pathways such as the ROS-mediated mTOR signaling pathway, ultimately culminating in testicular damage. This review synthesizes existing literature on how environmental exposures, including metals, air pollutants, industrial contaminants, and pesticides, disturb testicular homeostasis via autophagy-mediated oxidative stress, highlighting recent significant advancements. It also explores interventions like antioxidant support and autophagy regulation to alleviate testicular damage. These findings underscore the importance of elucidating the mechanisms of autophagy influenced by environmental exposures in disrupting the equilibrium of oxidative stress, identifying potential drug targets, and establishing a groundwork for enhancing future treatments and clinical management of testicular injuries.